Immunization with a novel recombinant protein (YidR) reduced the risk of clinical mastitis caused by Klebsiella spp. and decreased milk losses and culling risk after Escherichia coli infections - Tomazi, T. (2020)
The primary objective of this study was to evaluate the protective efficacy of a novel recombinant subunit vaccine containing the protein YidR (rYidR) against clinical mastitis (CM) caused by Klebsiella spp. and Escherichia coli. Given that E. coli infection is known to cause metritis, we also evaluated the effect of rYidR vaccination on the incidence of metritis and conception at the first artificial insemination. Retained placenta and abortion incidence, milk production and composition, and serological responses to specific antigens were also evaluated. In total, 3,107 cows were blocked by parity and randomly allocated into 1 of 3 treatment groups: experimental recombinant subunit vaccine containing the YidR protein (rYidR); commercial vaccine composed of Klebsiella pneumoniae siderophore receptors and porin protein (Kleb-SRP; KlebVax, Epitopix, Willmar, MN); and sterile water adjuvanted with aluminum hydroxide (20%; placebo). Vaccinations were performed at the dry-off for cows, and at 223 ± 3 d of pregnancy for pre-fresh heifers. A second administration was given at 21 ± 3 d after the first injection. Vaccination with rYidR significantly reduced the incidence of CM caused by Klebsiella spp. (3.2%) when compared with the placebo (5.1%) group. No difference was observed on risk of Klebsiella CM between Kleb-SRP (5.9%) and placebo groups. Cows in the rYidR group that experienced E. coli CM had a lower risk of death or culling (12.5%) compared with the Kleb-SRP (27.6%) and placebo groups (27.8%). Furthermore, among cows that developed E. coli CM, rYidR-immunized cows produced more milk than did cows in the placebo and Kleb-SRP groups. Regardless of CM occurrence, rYidR-immunized cows tended to have higher milk production up to the eighth month of lactation than cows in the other groups. No significant effect of treatment was observed on the overall incidence of abortion and metritis; however, the risk of retained placenta tended to be lower for the rYidR group (4.7%) compared with the placebo group (6.7%). In addition, primiparous cows in the rYidR group had the highest conception risk at the first artificial insemination (48.3%) compared with the placebo (39.5%) group, and no significant difference was observed when the Kleb-SRP (40.1%) group was compared with the placebo group. Generally, higher antibody serum titers (IgM and IgG) were observed for the immunized groups compared with the placebo. In conclusion, the rYidR vaccine reduced the risk of CM caused by Klebsiella spp. and the mortality or culling of cows with E. coli infections. Other benefits of the novel vaccine include maintenance of milk production after CM caused by E. coli, and higher conception risk at the first service in primiparous cows compared with cows in the placebo and Kleb-SRP groups.